Authentic learning through the case method in customized executive programs in Latin America - Campos Retana, Roy Alberto (2022)
The case method (CM) helps executives develop their problem-solving skills by exposing them to real-life situations in which they have to look for similarities and differences with respect to their professional contexts. This study seeks to explain how the analogies generated by the CM favor the authentic learning of experienced executives in custom executive programs (CEPs). An analogy is an explicit, nonliteral comparison between two objects, or sets of objects, that links their structural, functional, and causal similarities. Our comparative-case study, based on nine CEPs across six Latin American countries, seeks to identify the key factors that enable the effectiveness of the CM in authentic executive learning. Our results suggest that a CEP’s success, i. e., its ability to achieve the analogical knowledge transfer that authentic learning requires, in part depends on the CEP’s selection of cases and its appropriate delivery. Our analysis reveals two critical drivers of CM success in a CEP: choosing cases that enable analogies according to the type of business issues and constructing a CM narrative that illustrates the analogies of each case.